2017
DOI: 10.1371/journal.pone.0179236
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selected non-steroidal anti-inflammatory pharmaceuticals on microbial community assembly and activity in sequencing batch reactors

Abstract: This study covers three widely detected non-steroidal anti-inflammatory pharmaceuticals (NSAIDs), diclofenac (DCF), ibuprofen (IBP) and naproxen (NPX), as NSAIDs pollutants. The objective is to evaluate the impact of NSAIDs at their environmental concentrations on microbial community assembly and activity. The exposure experiments were conducted under three conditions (5 μg L-1 DCF, 5 μg L-1 DCF+5 μg L-1 IBP and 5 μg L-1 DCF+5 μg L-1 IBP+ 5 μg L-1 NPX) in sequencing batch reactors (SBRs) for 130 days. Removals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…For TCS, the removal was 89 ± 5% and 98 ± 1% (IBU+TCS reactors), only slightly lower than in reactors treating TCS alone. High removal efficiencies of anti-inflammatory drugs in aerobic treatment processes and low sorption potential of IBU on sludge have already been reported elsewhere [16]. In our case, removal efficiencies for TCS were mostly > 90%, both when fed alone or in combination with IBU.…”
Section: Bioreactor Performancesupporting
confidence: 84%
See 3 more Smart Citations
“…For TCS, the removal was 89 ± 5% and 98 ± 1% (IBU+TCS reactors), only slightly lower than in reactors treating TCS alone. High removal efficiencies of anti-inflammatory drugs in aerobic treatment processes and low sorption potential of IBU on sludge have already been reported elsewhere [16]. In our case, removal efficiencies for TCS were mostly > 90%, both when fed alone or in combination with IBU.…”
Section: Bioreactor Performancesupporting
confidence: 84%
“…Several studies examined the influence of pharmaceuticals on biological wastewater treatment processes, mainly focusing on the effects of pollutants on the efficiency of plants for their removal, microbial growth and the rate of COD and nutrients removal [15][16][17][18]. Arriaga et al reported a decrease of COD removal in conventional AS reactors fed with pharmaceuticals [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed an interactive effect of naproxen, carbamazepine and sulfamethoxazole on amphibian growth and development at environmental concentrations (Melvin et al 2014). Jiang et al (2017) showed that a mixture of naproxen, diclofenac and ibuprofen led to an increase in bacterial diversity in a sequencing batch reactor. According to the Shannon-Wiener diversity index, Actinobacteria and Bacteroidetes were enriched, whereas the number of Micropruina and Nakamurella decreased after the addition NSAIDs.…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 99%